Drug-resistant Salmonella Typhi induced kidney injury with rhabdomyolysis: A case report, and literature review. (2021) - Ata, Fateen; Marzouk, Sandy Kamil Kamal; Bilal, Ammara Bint I.; Khan, Adeel Ahmed; Ibrahim, Ezzedin; Almadani, Mohammed Taha Mahmood
Highlights: AKI secondary to Salmonella Typhi can present with rhabdomyolysis. Patients may require temporary dialysis with a prolonged hospital stay. The prognosis of ST induced rhabdomyolysis is excellent. We present an extensive literature review of all reported ST bacteremia cases with AKI secondary to rhabdomyolysis. Abstract: Salmonella Typhi (ST) is a rod-shaped gram-negative bacterium that infects humans via contaminated food or water. Humans are the only reservoirs for the bacteria. Infection usually manifests as fever, abdominal pain, and diarrhea. However, complications such as intestinal perforation, hepatosplenomegaly, and renal injury can occasionally occur. Acute kidney injury (AKI) is associated more commonly with ST than other bacteria causing gastrointestinal (GI) infections. The exact pathophysiology of AKI in ST infection is unknown. One of the rarely reported mechanisms is rhabdomyolysis. We present a similar case of resistant ST infection leading to AKI with rhabdomyolysis. This article also contains an extensive literature reviews of all reported ST bacteremia cases with AKI secondary to rhabdomyolysis.